Ideas Pattern Manifested in Rhetorical Moves of English Language Teaching and Learning Research Articles Discussion Written by Indonesian English Academics - Asari, Slamet; Kurnia, Fabiola D.; Suharsono, Suharsono (ELite Journal : International Journal of Education, Language and Literature, 2018)
Ideas pattern manifested in the presentation of rhetorical Moves can be viewed as another angle to determine ones rhetorical or thought pattern. Writing research report requires writers discourse competence to effectively present their argument and persuasive appeal particularly on the Discussion section of a research article. This can be realized through the presentation of Rhetorical Moves employed by writers. This qualitative study attempts to examine rhetorical Moves employed by Indonesian English academics in writing out English Language Teaching and Learning (ELTL) research articles. It also seeks to determine thought patterns of those writers as reflected in the rhetorical Moves used. There were 89 articles used as data source taken from 4 journals to be analyzed employing Swales CARS model (1990) on research article Discussion as parameter. It revealed that ELTL research articles Discussion written by Indonesian English academics employed 4 Moves consistently with 4 other Moves were absent. However, the idea pattern delivered was substantially logic, coherent, and linearly fashioned. Keywords: Ideas pattern, Rhetorical Moves, Research Article, English Language Teaching and Learning (ELTL).